Central and Local Approaches to Transitional Justice - Subia, Julianne (Student Undergraduate Research E-journal!, 2017)
This paper aims to examine the relationship between central and local approaches to transitional justice in postconflict situations. It is found that these two levels are not as ‘neat’ as some may suggest, and actors from both levels behave in ways more commonly attributed to the other level. By thinking of them in dynamic and behavioral rather than static and spatial terms, the (inter)relationship might be better understood. This is important as transitional justice is increasingly employed and local approaches (sometimes uncritically) are sought after.